Economic Diversification in LICs : Stylized Facts and Macroeconomic Implications - Papageorgiou, Chris (Staff Discussion Notes; Staff Discussion Notes ;, 2012)
Limited diversification is an underlying characteristic of many low-income countries (LICs). Concentration in sectors with limited scope for increases in productivity and quality may result in less broad-based and sustainable growth. Moreover, lack of diversification may increase exposure to adverse external shocks and macroeconomic instability. The SDN will have three objectives. First, to review and extend the evidence, from the existing literature and ongoing IMF work, that points to diversification as a crucial aspect of the development process. A major focus will be on cross-country and cross-regional differences in the pace of diversification. Second, to draw lessons from the experiences of those countries that have successfully diversified their economies. Third, to analyze the relationship between diversification, growth, and volatility.